Pengaruh Harga, Citra Destinasi, Dan Media Sosial Terhadap Keputusan Berkunjung Wisatawan Pada Pintu Langit Prigen Pasuruan: Studi Pada Wisatawan Pintu Langit Prigen - Lia Alifiah (Politeknik Kampar, 2023)
This study aims to determine the effect of price, destination image, and tourists' visiting decisions at the Prigen Pasuruan sky gate. This type of research is quantitative research. The population in this study are some of the tourists who have visited the Prigen Pasuruan sky gate tour, the sample of this study is 150 respondents, data source from this research is primary data source. The data collection technique used was a questionnaire. The data analysis tool used is multiple linear regression analysis with the help of SPSS 24 software. The results of this study indicate (1). Price has a significant influence on the decision to visit. (2). Destination image has a significant effect on visiting decisions. (3). Social media has a significant effect on visiting decisions. (4). price, destination image, social media simultaneously influence the decision to visit.